TERMINOLOGICAL METAPHORS IN V. A. BOGORODITSKY’S SCIENTIFIC DISCOURSE - Leonidovna Ariskina, Olga; Viktorovich Pulov, Evgeny (Revista Inclusiones, 2020)
The objective of current research is to analyze the metaphors that function in V.A. Bogoroditsky’s scientific text as a means of representation of scientific discourse’s linguo-cognitive characteristics. The research draws on such scientific methods as analysis of the linguistic personality proposed by Y.N. Karaulov and George Lakoff’s cognitive metaphor theory. The results of the research can be applied in a number of academic courses ("Teacher’s professional personality", "Genres of academic discourse", "Problems of terminological nomination", etc.), and they may also be essential in developing continuing education (lifelong) courses for teachings staff specialising in "Mentor’s linguistic personality: history and contemporaneity". The theoretical and practical significance of the obtained conclusions is determined by the novelty of the research: V.A. Bogoroditsky’s writings have been analyzed in the anthropocentric context for the first time. The prospects for further study is seen in making the comparative analysis of V.A. Bogoroditsky’s terminological metaphors and those of his teacher, an outstanding linguist I.A. Baudouin de Courtenay.